Effectiveness of monetary policy transmission in Indonesia - Muhammad Khoirul Fuddin (Economic Journal of Emerging Markets, 2014)
This study discusses the channel of monetary policy transmission mechanism of money, credit, interest rate and exchange rate in Indonesia. The effectiveness of the transmission mechanism of monetary policy in Indonesia can be described and explained by the ultimate target object in Indonesia, specifically economic growth and inflation. The analytical tool used in this study is Vector Error Correction Model (VECM) which uses impulse response and variance decomposition in determining the effectiveness of monetary policy transmission mechanism. The results explain that the credit channel is considered effective in explaining economic growth and the interest rate channel is effective in explaining inflation found in Indonesia.